Mama Jaky: The Journey of a Mother - Bernardi, Paolo (Italy, 2014)
The journal of a 22 Tanzanian pregnant woman whose due day is delayed. The story follows mama Jaky during her daily life and her efforts to deliver her baby.
Verzio Film Festival Submission
Verzio Film Festival Submission
Keywords: Documentary films